Subtypes of Major Depression in Substance Dependence - Niciu, Mark J. (2009)
AIMS: This study evaluated features that differentiate subtypes of major depressive episode (MDE) in the context of substance dependence (SD). DESIGN: Secondary data analysis using pooled data from family-based and case-control genetic studies of SD. SETTING: Community recruitment through academic medical centers. PARTICIPANTS: 1,929 unrelated subjects with alcohol and/or drug dependence. MEASUREMENTS: Demographics, diagnostic criteria for psychiatric and substance use disorders, and related clinical features were obtained using the Semi-Structured Assessment for Drug Dependence and Alcoholism. We compared four groups: no lifetime MDE (no MDE), independent MDE only (I-MDE), substance-induced MDE only (SI-MDE), and both types of MDE. FINDINGS: Psychiatric measures were better predictors of MDE subtype than substance-related or sociodemographic ones. Subjects with both types of MDE reported more lifetime depressive symptoms and co-morbid anxiety disorders and were more likely to have attempted suicide than subjects with I-MDE or SI-MDE. Subjects with both types of MDE, like those with I-MDE, were also more likely than subjects with SI-MDE to be alcohol dependent only than either drug dependent only or both alcohol and drug dependent. CONCLUSIONS: SD individuals with both types of MDE have greater psychiatric severity than those with I-MDE only or SI-MDE only. These and other features that distinguish among the MDE subtypes have important diagnostic and potential therapeutic implications.